Beyond the Floor: Traumatic Medial Rectus Entrapment in a Medial Orbital Wall Fracture Presenting with Diplopia and Retinal Hemorrhage - Pratistha Satyanegara; Mardijas Efendi (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2025)
Background: Medial orbital wall fractures with extraocular muscle entrapment represent a significant but less common variant of orbital trauma compared to floor fractures. These injuries pose a diagnostic and management challenge, with the potential for severe, long-term functional deficits and life-threatening systemic complications if not addressed promptly. This report details a case of medial rectus muscle entrapment complicated by a concurrent posterior segment injury. Case presentation: A 21-year-old male presented to the emergency department following a motorcycle accident, sustaining blunt trauma to his left eye. He reported an acute onset of blurred vision and binocular diplopia. Ophthalmic examination revealed a visual acuity of 20/80 in the left eye. There was a manifest esotropia and a profound abduction deficit, with marked restriction of movement on attempted lateral, superolateral, and inferolateral gaze. The forced duction test was positive, confirming mechanical restriction. Funduscopy identified significant retinal hemorrhages. A maxillofacial computed tomography scan confirmed a comminuted fracture of the left medial orbital wall (lamina papyracea) with clear evidence of medial rectus muscle entrapment within the fracture fragments. The patient underwent urgent surgical intervention involving exploration of the medial orbit, careful release of the incarcerated medial rectus muscle, and anatomical reconstruction of the wall with a titanium mini-plate. Intraoperative forced duction testing confirmed complete resolution of the mechanical restriction. Postoperatively, the patient showed free passive ocular motility, although active movement was recovering, and the retinal injuries required continued observation. Conclusion: This case underscores the critical importance of maintaining a high index of suspicion for medial rectus entrapment in patients presenting with post-traumatic diplopia and an abduction deficit. A thorough clinical examination, particularly the forced duction test, is paramount and often more definitive than imaging alone. Urgent surgical decompression and reconstruction are imperative to prevent permanent strabismus from muscle ischemia and to mitigate the risk of the oculocardiac reflex. Furthermore, the presence of concomitant intraocular injuries, such as traumatic retinopathy, must be diligently assessed as they significantly impact the final visual prognosis.